The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1994
DOI: 10.1111/j.1469-8749.1994.tb11796.x
|View full text |Cite
|
Sign up to set email alerts
|

Children With Myelomeningocele: The Impact of Disability on Family Dynamics and Social Conditions a Nordic Study

Abstract: SUMMARY Family dynamics and social conditions were studied of 527 children with myelomeningocele aged four to 18 years from Denmark, Finland, Norway and Sweden; the control group was a representative sample of 7792 children of the same age‐range and from the same countries. Information was obtained from postal questionnaires and from patients' charts. Overall, there were more similarities than differences between index and control families, the major difference occurring in measures related to the mothers' sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…A Swedish study from 1992 found differences according to severity of impairment on employment, as we did . A Nordic study from 1994 on children with myelomeningocele found that 66% of mothers of the disabled children were working or studying full‐time versus 77% of the mothers of children without disability. It is remarkable that the social welfare systems in the Nordic countries and Canada seem to succeed in keeping employment high for mothers even after they have given birth to a child with a disability.…”
Section: Discussionsupporting
confidence: 58%
“…A Swedish study from 1992 found differences according to severity of impairment on employment, as we did . A Nordic study from 1994 on children with myelomeningocele found that 66% of mothers of the disabled children were working or studying full‐time versus 77% of the mothers of children without disability. It is remarkable that the social welfare systems in the Nordic countries and Canada seem to succeed in keeping employment high for mothers even after they have given birth to a child with a disability.…”
Section: Discussionsupporting
confidence: 58%
“…A study comparing the family dynamics and social conditions of 527 Nordic families of 4-to 18-year-old children with myelomeningocele to a control group of 7792 children reported more similarities than differences between the families (Lie et al 1994). The majority of the scores on the measures were not statistically different across adolescents/young adults, mothers, fathers, and siblings in the three groups.…”
Section: Discussionmentioning
confidence: 91%